REXIB: Remote Experiments Interface Builder - Jorge R. Alves (2006)
Remote Experimentation is an educational resource that allows teachers to strengthen the practical contents of science & engineering courses. However, building up the interfaces to remote experiments is not a trivial task. Although teachers normally master the practical contents addressed by a particular remote experiment they usually lack the programming skills required to quickly build up the corresponding web interface. This paper describes the automatic generation of experiment interfaces through a web-accessible Java application. The application displays a list of existent modules and once the requested modules have been selected, it generates the code that enables the browser to display the experiment interface. The tools main advantage is enabling non-tech teachers to create their own remote experiments.